Letramento acadêmico no ensino médio: uma experiência pedagógica a partir do material didático autoral “Manual do Jovem Pesquisador” - Palacios, Graciela Gomes (2017)
This investigations was carried out during the Language Teaching Professional Master's Degree Course, aiming the socialization of a pedagogical product with education professionals, in order to contribute to the learning and teaching process, above all Portuguese Language classes investigative practices process. Thus, this dissertation brings reflections around the elaboration process, implementation and redesign of an authorial teaching material that aimed support scientific methodology teaching trough academic literacy practices in Portuguese subject, in first year of High School. The pedagogical product, named "Young Researcher Manual", was organized around three academic sphere genres, embracing the stages of planning, execution and socialization of scientific research. The adopted speech genre notion belongs to the bakhtinian root and it was updated to Portuguese Language teaching context by Bunzen and Mendoza (2012, p.12), as cultural stabilized textualdiscursive organization shapes. In order to speak about literacy practices, I took as a reference the definition which says that they refer "to the behavior and to the social and cultural conceptualizations that confer a sense to writing and/or reading uses¨. The intervention was developed by the researcher- teacher and class conductor, in a public school in Porto Alegre, with High School first year students and had as objectives: the critical comprehension of the pedagogical process developed, the analysis of the main advances and learning difficulties identified during this process and the material improvement. The methodology that guided the intervention was the action research that places the professional development subordinate to the relation among action, investigation and formation (LATORRE, 2003). For the purpose of reaching the research objectives, the analysis verified if there were advances in language use and in research practices comprehension through diagnostic questionnaires, self evaluation, writing and rewriting of the articulators genres and the set of tasks evaluation made by the students. Considering the results, it was possible to notice, among students who were considered paticipative, an improvement related to the understanding of what it is and what is the research at school for. Furthermore, the analyses of the productions revealed advances on the usage of the language. The implementation of the material presented its strengths and weaknesses and, with that, it was possible to invest in its re-elaboration.